Temperate and virulent Lactobacillus delbrueckii bacteriophages: comparison of their thermal and chemical resistance - Ebrecht, Ana Cristina (2010)
The aim of this work was to study the efficiency of diverse chemical and thermal treatments usually used in dairy industries to control the number of virulent and temperate Lactobacillus delbrueckii bacteriophages. Two temperate (Cb1/204 and Cb1/342) and three virulent (BYM, YAB and Ib3) phages were studied. The thermal treatments applied were: 63 degrees C for 30 min (low temperature--long time, LTLT), 72 degrees C for 15 s (high temperature--short time, HTST), 82 degrees C for 5 min (milk destined to yogurt elaboration) and 90 degrees C for 15 min (FIL-IDF). The chemical agents studied were: sodium hypochlorite, ethanol, isopropanol, peracetic acid, biocides A (quaternary ammonium chloride), B (hydrogen peroxide, peracetic acid and peroctanoic acid), C (alkaline chloride foam), D (p-toluensulfonchloroamide, sodium salt) and E (ethoxylated nonylphenol and phosphoric acid). The kinetics of inactivation were drew and T(99) (time necessary to eliminate the 99% of phage particles) calculated. Results obtained showed that temperate phages revealed lower resistance than the virulent ones to the treatment temperatures. Biocides A, C, E and peracetic acid showed a notable efficiency to inactivate high concentrations of temperate and virulent L. delbrueckii phages. Biocide B evidenced, in general, a good capacity to eliminate the phage particles. Particularly for this biocide virulent phage Ib3 showed the highest resistance in comparison to the rest of temperate and virulent ones. On the contrary, biocide D and isopropanol presented a very low capacity to inactivate all phages studied. The efficiency of ethanol and hypochlorite was variable depending to the phages considered. These results allow a better knowledge and give useful information to outline more effective treatments to reduce the phage infections in dairy plants.